2007
DOI: 10.1177/1367493507079571
|View full text |Cite
|
Sign up to set email alerts
|

Peer victimization in children with attention-deficit hyperactivity disorder

Abstract: This study examined the correlation of peer victimization to psychosocial adjustment in a sample of children diagnosed with attention-deficit hyperactivity disorder (ADHD). A total of 303 files of youth who received a psycho-educational assessment were reviewed; of these, 116 had an ADHD diagnosis. The data collected included the Child Behavior Checklist (which includes items assessing peer victimization), Conner's Parent Rating Scale, Revised Children's Manifest Anxiety Scale and Children's Depression Invento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
48
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 28 publications
5
48
1
1
Order By: Relevance
“…This pattern was particularly likely for girls with ADHD versus comparison girls. Humphrey et al (2007) found that children with ADHD and a comorbid diagnosis, especially a disruptive disorder, are at high risk of victimization.…”
Section: Victimizationmentioning
confidence: 97%
“…This pattern was particularly likely for girls with ADHD versus comparison girls. Humphrey et al (2007) found that children with ADHD and a comorbid diagnosis, especially a disruptive disorder, are at high risk of victimization.…”
Section: Victimizationmentioning
confidence: 97%
“…A large magnitude effect size was predicted based on established large magnitude relationships (effect sizes≥1.9) between working memory tasks and ADHD symptoms (Kofler et al 2010;Rapport et al 2009) and between ADHD symptoms and social problems (r=0.53 to 0.61; Andrade et al 2009;Humphrey et al 2007). Mediation analysis using the bias-corrected bootstrapping procedure requires 34 total participants to achieve 0.80 power (Fritz and MacKinnon 2007).…”
Section: Power Analysismentioning
confidence: 99%
“…1 path a*b). This hypothesis is based on previous findings indicating that working memory deficits are related functionally to inattentive and hyperactive behaviors (Kofler et al 2010;Rapport et al 2009), which in turn, are correlated highly with social problems (Andrade et al 2009;Humphrey et al 2007). The hypothesized indirect effect would thus indicate that one or more of the hallmark ADHD symptoms (inattention, impulsivity-hyperactivity) that occur because of working memory failure (e.g., interrupting others due to an inability to store intended speech temporarily while interacting with others) contribute significantly to the social problems experienced by children with ADHD.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Indeed, research suggests that youth with learning and developmental disabilities are at risk of peer victimization (Baumeister, Storch, & Geffken, 2008;Humphrey, Storch, & Geffken, 2007;Marini, Fairbairn, & Zuber, 2001;Sanchez, & Cerezo, 201 O;Saylor & Leach, 2009;. However, it is evident that rates of victimization vary by disability type and context (see review by Rose, Monda-Amaya, & Espelage, 2011 ).…”
mentioning
confidence: 99%